The role of medical students' training and community placement as a tool to enhance medical education in Canada. (2nd January 2019) - Jozaghi, Ehsan; Yake, Kevin; Maynard, Russ; Blyth, Sarah
ABSTRACT: We are currently witnessing unprecedented crises on an international scale linked to synthetic opioid overdose fatalities. While most governments and health policy makers have focused mainly on combating the current crises through harm reduction strategies, little focus has been given to the role and training of future doctors in evidence-based practices of harm reduction and addiction medicine. Therefore, enhancing medical student's training in the implementation of addiction medicine, and the establishment (or expansion) of medical students, residents and post-fellows' community placement—via partnerships with organizations that provide specialized care to patients struggling with mental health and addiction—would strongly improve the health and well-being of marginalized populations.